The Development and Validation of the SWADOC: A Study Protocol for a Multicenter Prospective Cohort Study - Mélotte, Evelyne; Belorgeot, Marion; Herr, Roxanne; Simon, Jessica; Kaux, Jean-François; Laureys, Steven; Sanz, Leandro R. D.; Lagier, Aude; Morsomme, Dominique; Pellas, Frederic; Gosseries, Olivia (Frontiers in Neurology, 2021)
Background: After a coma, patients with severe brain injury may present disorders of consciousness (DOC). A substantial proportion of these patients also suffer from severe dysphagia. Assessment of and therapy for swallowing disabilities of patients with DOC are essential because dysphagia has major functional consequences and comorbidities. Dysphagia evaluation in patients with DOC is impeded by the lack of adapted tools. The first aim of this study was to create a new tool, the SWallowing Assessment in Disorders Of Consciousness (SWADOC), and propose a validation protocol. The SWADOC was developed to help therapists assess factors related to swallowing in patients with DOC. The second aim was to investigate the relationship between patients' level of consciousness and SWADOC items and scores. Method/Design: In this multicenter prospective cohort, 104 patients with DOC will be tested three times over five consecutive days with the SWADOC. Statistical analyses will focus on the reliability and validity of the SWADOC, especially the intrarater and interrater reliability, internal consistency, measures of dispersion, and concurrent validity with the Facial Oral Tract Therapy Swallowing Assessment of Saliva (FOTT-SAS). The level of consciousness will be assessed with the Simplified Evaluation of CONsciousness Disorders (SECONDs) and the Coma Recovery Scale-Revised (CRS-R). Discussion: The assessment of swallowing abilities among patients with DOC is the first necessary step toward the development of a customized dysphagia care plan. A validated scoring tool will be essential for clinicians to better assess dysphagia in patients with DOC and document the evolution of their disorders. Trial Registration: NCT04706689.